Desempenho econômico-financeiro de indústrias calçadistas brasileiras: uma análise do período de 2000 a 2006 - Azeredo, Adriano José (Universidade do Vale do Rio do Sinos, 2008)
The objective of this study is to evaluate the economic and financial performance of the Footwear Industry from the 1980’s on, when the competitive market crossed the domestic frontier, demanding more efficiency from shoemaking companies regarding the management of their activities. Within this context, accountancy is seen as one of the necessary information sources to guide the proper use of resources. The study is exploratory, quantitative and documental in nature. Statements of financial accounting from 15 Brazilian shoemaking companies located in the South, Southeast and Northeast regions were collected from the year 2000 to 2006. The study was based on 30 selected indexes, which made possible to analyze the group of companies by the standard-index of each indicator. Following that, the index analysis of each company was made. In order to check the analysis results, typical value techniques were used as a comparative measure of the standard indexes and the statistical correlation tests. The companies ran
Keywords: demonstrações contábeis; desempenho econômico-financeiro; indicadores; índices-padrão; ranking; análise - indústria calçadista; economic-financial performance; financial accounting statement; indicators; ranking; shoemakers; standard index; analysis footwear industry; Ciências Sociais Aplicadas